Contribution of Occupational Health to multidisciplinary team work for COVID-19 prevention and management - Gross, J Valérie; Fritschi, Lin; Mohren, Judith; Wild, Ursula; Erren, Thomas C (La Medicina del Lavoro, 2021)
Introduction: The SARS-CoV-2/Covid-19 pandemic is a challenge for public health and occupational medicine and developing prevention and protection strategies needs expertise from many disciplines. To make prevention successful, individuals have to be motivated to participate and, in turn, motivation depends on understanding how and why prevention measures are implemented. We present a structured approach (the Cycle of prevention) which involves different stakeholders and perspectives to develop, and monitor, prevention strategies in transparent and effective ways.